PENGARUH LATIHAN LOMPAT TALI DENGAN CEPAT TERHADAP KECEPATAN PAD A TIM TENIS MEJA PUTRA SMA NEGERI OLAHRAGA PROVINSI RIAU - Faizin, Anda Dinu; Juita, Ardiah; ', Slamet (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problems raised in this research is that the athlete’s speed is still below average, this can be comprehended from various experiments and in both of friendly and official match; which become one of the losing factors.The type of the research is experimental research that aimed to perceive the impact of the exercises form. The purpose of the research is to acknowledge the influence of skipping exercise on the speed of table tennis man’s team in Physical Education High School, Riau Province. The population in the research is the team of Table Tennis Team in SMA NegeriOlahraga, Riau Province, in which there are 6 persons in the team.The technique of taking the sample is by using total sampling; where the total amount of the population is becoming the sample. The instrument in the research utilizes sprinting test in 50 meter distance as a means to measure the speed.The analysis is conducted by using test-t. Based on the data of the analysis and discussion, it proves that Tcountin the amount of 2.876 and Ttable 2.015. It means that Tcount>Ttable. on the level ɑ=0,05. As the result, it can inferred that there is a significant influence on the skipping exercise on the speed of table tennis man’s team in SMA NegeriOlahraga, Riau Province. Key Words: Skipping Speed, Table Tennis